2020
DOI: 10.17582/journal.aavs/2020/8.4.385.391
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hepato-Renal Protective Activity of Ocimum basilicum Leaf Extract against Paracetamol Toxicity in Rat Model

Abstract: Kidneys has an important role in removing wastes like

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
5
12
0
1
Order By: Relevance
“…In the present study, AEAASB caused a significant decrease in MDA levels and an increase in SOD, CAT, and GSH levels in the liver and kidney. These results are in line with those obtained by Soliman et al [13] who showed that the ethanolic extract of O. basilicum prevented paracetamol toxicity by enhancing the antioxidant status by decreasing MDA levels and increasing antioxidant enzyme levels in liver and kidney tissue. In addition, the results of in vitro antioxidant tests showed that AEAASB is a very strong antioxidant (IC 50 = 180 μg/ml, AAI = 5:55) that has the ability to scavenge 63.03% of DPPH• radicals and reduce ferric iron by 52.68 mgEqVitC/100 g DM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, AEAASB caused a significant decrease in MDA levels and an increase in SOD, CAT, and GSH levels in the liver and kidney. These results are in line with those obtained by Soliman et al [13] who showed that the ethanolic extract of O. basilicum prevented paracetamol toxicity by enhancing the antioxidant status by decreasing MDA levels and increasing antioxidant enzyme levels in liver and kidney tissue. In addition, the results of in vitro antioxidant tests showed that AEAASB is a very strong antioxidant (IC 50 = 180 μg/ml, AAI = 5:55) that has the ability to scavenge 63.03% of DPPH• radicals and reduce ferric iron by 52.68 mgEqVitC/100 g DM.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the high level of MDA and low levels of GSH, SOD, and CAT were observed in the group of untreated animals that received paracetamol (negative control). Substances that increase GSH, SOD, and CAT levels and decrease MDA levels are known to inhibit paracetamol-induced liver and kidney injury formation [ 13 ]. In the present study, AEAASB caused a significant decrease in MDA levels and an increase in SOD, CAT, and GSH levels in the liver and kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renoprotective effect against diabetes induced renal affection in albino rats 500 mg/kg of body weight/day; given to rats through gastric tube for six weeks) [120] Leaves Ethanolic extract Rats Hepato-renal protective against paracetamol toxicity in rat model 200-400 mg/kg of body weight; once daily for 30 consecutive days) [121] Aerial parts Hydroalcoholic extract Rats…”
Section: Aerial Partsmentioning
confidence: 99%
“…Pemberian Paracetamol secara oral pada peneliti (Soliman et al, 2020) dengan dosis 500 mg/kgBB selama 30 hari menyebabkan peningkatan yang signifikan pada kadar trigliserida. Pada kelompok tikus yang diberikan paracetamol dengan dosis 500 mg/kgBB dan Ekstrak kemangi dosis 200 mg/kgBB selama 30 hari mengalami penurunan.…”
Section: B Pembahasanunclassified